2021
DOI: 10.4236/ojog.2021.112018
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Cytopathological Profile of Dysplastic Lesions of the Cervix in South-Kivu/Dr Congo

Abstract: Background: Cervical cancer is one of the most common cancers in women in the world. The recrudescence of dysplastic lesions is increasing, especially in developing countries, because of the absence of screening. The objective of this work is to determine the prevalence of dysplastic lesions of the cervix in women who are sexually active in South Kivu province. Methods: It was a cross-sectional, descriptive and analytical study of 625 women who came for gynecological consultation, all of whom had cervical-uter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
1
1
Order By: Relevance
“…• In 2019, the study by Nyakio et al in South Kivu (Eastern DRC) found a prevalence of 14.72% of cytological abnormalities in women in sexual activity [8]. Contrary to our study, the risk is multiplied by two in women with prolapse.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…• In 2019, the study by Nyakio et al in South Kivu (Eastern DRC) found a prevalence of 14.72% of cytological abnormalities in women in sexual activity [8]. Contrary to our study, the risk is multiplied by two in women with prolapse.…”
Section: Discussioncontrasting
confidence: 85%
“…This could be extrapolated from data in sub-Saharan Africa. [7] In 2019, the study conducted by Nyakio et al in Bukavu (eastern of the Democratic Republic of the Congo) found a prevalence of 14.72% of cervical cytopathological abnormalities in the general female population, with 5.28% of cervical dysplasia [8].…”
Section: Introductionmentioning
confidence: 99%